2021
DOI: 10.1186/s12886-021-01985-5
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of the progression of rhegmatogenous retinal detachment on patients with the fourteen-day quarantine in the early period of COVID-19 outbreak

Abstract: Backgrounds The COVID-19 Pandemic has a great impact on hospitals and patients. The 14-day quarantine caused surgery of rhegmatogenous retinal detachment (RRD) postponed. We aimed to explore the risk factors of RRD progression in a group of patients whose surgery was postponed during the top-level emergency response of COVID-19. Methods A retrospective case series. Medical records of all consecutive patients with a diagnosis of RRD who underwent a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Patient selection bias is unavoidable. A delay in the treatment can produce a worse clinical situation due to the progression of PVR, CD [ 50 ], which are known as the most common cause of failure in retinal detachment surgery [ 49 , 51 ]. We failed to show the effect of presurgery waiting time and severity of PVR on the outcome of surgery or the choice of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection bias is unavoidable. A delay in the treatment can produce a worse clinical situation due to the progression of PVR, CD [ 50 ], which are known as the most common cause of failure in retinal detachment surgery [ 49 , 51 ]. We failed to show the effect of presurgery waiting time and severity of PVR on the outcome of surgery or the choice of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study from Northern England showed a similar observation [ 30 ]. Of note, a 14-day delay in RD surgery due to quarantine led to a worse outcome [ 31 ]. We observed an almost equal incidence of RD in COVID and non-COVID groups.…”
Section: Discussionmentioning
confidence: 99%